(untitled) (Journal of Dhaka Medical College, 2020)
Background: Autism is a complex neurodevelopmental disorder and one of the major cause of lifelong disability. Magnesium, calcium and iron are important minerals of biological system. Hypomagnesaemia, hypocalcaemia and iron deficiency has been found to be associated with abnormal metabolic functions resulting in autistic spectrum disorder. Hypothesis: Serum magnesium, calcium and iron levels are lower in ASD children than healthy control. Objective: To measure serum magnesium, calcium and iron in ASDchildren and to compare them with healthy control. Method: This observational type of analytical study with case-control design was conducted in the Department of Physiology, Bangabandhu Sheikh Mujib Medical University, Shahbag, Dhaka from March 2014–January 2016. For this study, 80 children aged 3-10 years were randomly selected, among which 40 were apparently healthy and 40 were diagnosed as ASD. The study group was selected from the Parents’ Forum (Mohakhali DOHS, Dhaka) for ASD children and the control group was selected from some regular schools. 5ml venous blood was collected from both groups for analysis of fasting serum magnesium, calcium and iron. Fasting magnesium, calcium and iron were estimated in all children by standard laboratory method. Independent sample‘t’ test and proportion (Z) test were used for statistical analysis. P value Â0.05 was accepted as significant. Result: The mean serum magnesium, calcium and iron were significantly lower (pÂ0.001) in cases as compared to controls. The frequency of hypomagnesaemia, hypocalcaemia and iron deficiency were significantly higher in early diagnosed ASD children, which was 7 (17.5%), 22 (55%) and 5 (12.5%) out of 40 ASD children respectively.The mean values of all the biochemical variables in normal children were within normal ranges. Conclusion: The results indicate that hypomagnesaemia, hypocalcaemia and iron deficiency are common in ASD children. J Dhaka Medical College, Vol. 27, No.2, October, 2018, Page 199-204